Biofilm dispersal: deciding when it is better to travel. Issue 4 (29th September 2014) - Wood, Thomas K.
Summary Bacteria live predominantly in biofilms, and the internal signal cyclic diguanylate (c‐di‐GMP) is a universal signal that governs the formation and the dispersal of these communities. Pseudomonas aeruginosa is one of the most important reference systems for studying bacterial biofilms and contains numerous diguanylate cyclases (DGCs) for synthesizing c‐di‐GMP and phosphodiesterases (PDEs) for degrading c‐di‐GMP. However, few studies have discerned how cells in biofilms respond to their environment to regulate c‐di‐GMP concentrations through this sophisticated network of enzymes. Basu Roy and Sauer (2014) provide insights on how cells disperse in response to an increase in nutrient levels. Their results show that the inner membrane protein NicD is a DGC that controls dispersal by sensing nutrient levels: when glutamate concentrations are increased, NicD is dephosphorylated, which increases c‐di‐GMP levels and leads to phosphorylation and processing of dispersal regulator BdlA. Processing of BdlA leads to activation of PDE DipA, which results in a net reduction of c‐di‐GMP and biofilm dispersal. These results suggest biofilm dispersal relies on surprisingly dynamic c‐di‐GMP concentrations as a result of a sophisticated interaction between DGCs and PDEs.